PERANCANGAN SISTEM INFORMASI PENDAFTARAN PESERTA DIDIK BARU (PPDB) BERBASIS WEB MENGGUNAKAN METODE RAPID APLLICATION DEVELOPMENT (RAD) - Anton Yudahana; Imam Riadi; Ade Elvina (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
One of the Raudhatul Athfals chosen by parents to enroll their children in schools within the context of playgroups overseen by the Sikka District's ministry of religion is RA Plus Rabbani. However, this school hasn't made use of the information system as a tool for system management, particularly when it comes to new student registration. A yearly administrative procedure is the registration of new students, and if the implementation is still done the old-fashioned way, it will affect how inefficient the process is. As a result, coordinating the registration of new students requires the use of a computerized system. The plan will be to use the Rapid Application Development (RAD) method to create a web-based information system. Flowcharts and Data Flow Diagrams (DFD) are supporting tools used in system design, together with Entity Relationship Diagrams (RAD) for database design analysis and Figma for system interface design study. The results of the research show that RAD can support system development in a shorter time compared to other methods such as waterfall, SDLC, and prototype. Based on the discussion, it is concluded that the design of the system created can make it easier for users to use the system, because the design made is more attractive and easy to understand for various groups.